The love of nature: Imaginary environments and the production of ontological security in postnatural times. Issue 1 (28th March 2022) - Pohl, Lucas; Helbrecht, Ilse
Abstract: The existence of nature is vehemently called into question in the Anthropocene. The standard image of nature as a pristine, harmonious, and stable background no longer holds, especially as ecological changes increasingly penetrate the collective consciousness. Consequently, there has been growing interest in the psychological effects of this end of nature. A recent wave of scholarship shows how climate change and the Anthropocene more generally affect people's daily lives and present significant threats to psychic well‐being. This paper follows on from these debates. In contrast, however, we ask if and how nature is still considered as providing a subjective sense of (ontological) security today. We argue that, even under postnatural conditions, nature still maintains an imaginary existence in the social reality of the subject. We address this argument empirically by focusing on everyday life perceptions of nature in the city of Vancouver, British Columbia, and theoretically by following the psychoanalyst Jacques Lacan. Drawing on image‐based interviews (photo‐elicitation), we demonstrate that a psychoanalytic approach to imaginary environments allows us to understand why people state that they love nature even though it does not exist. We show how this love works by pointing out how nature is considered as (m)other and, through this, engaged as a place to retreat and escape from the burdens of everyday life while being perceived from a certain distance. In conclusion, we emphasise the broader political consequences of the imaginary existence of nature and call for further engagement with the persistence of nature's fantasy in times when nature seems to no longer fit the purpose. Abstract : There has been little attention given to how nature can provide a sense of security in times of the Anthropocene. Based on image‐based interviews conducted in Vancouver, BC, and inspired by psychoanalytic theory, this paper aims to understand how, even under today's "postnatural" conditions, nature still persists as an imaginary in the social reality of urban everyday life.